Comparison of microscopic vs. endoscopic technique in revision stapes surgery: a systematic literature review - Gioacchini, Federico Maria; Ralli, Massimo; Re, Massimo; Iannella, Giannicola; Scarpa, Alfonso; Di Pasquale Fiasca, Valerio; Motta, Giovanni; Di Stadio, Arianna (Frontiers in Audiology and Otology, 2025)
IntroductionIn this study, we aimed to evaluate the differences in hearing outcomes and surgical complications after revision stapes procedure using endoscopic and microscopic techniques.MethodsSystematic literature review was performed following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) checklist. A comprehensive search with timeline from January 2010 to May 2024 was performed using PubMed, Scopus, and Google Scholar databases. The following keywords were used: “otosclerosis revision surgery and outcome,” “otosclerosis revision and endoscopic surgery,” “otosclerosis revision surgery and quality of life,” “otosclerosis revision surgery and indication,” “otosclerosis revision surgery and risk,” “otosclerosis revision surgery and results.” Only articles published in English were included. Data on the causes of reintervention, audiological tests, and post-surgical complications were extracted, analyzed, and compared.ResultsFourteen studies, involving 686 patients and 690 procedures, were included. All articles had a retrospective cohort design, with the number of included patients ranging from 6 to 156. Revision surgery was prevalently performed for recurrence of conductive hearing loss (420 cases, 60.8%). Twelve procedures were performed using an endoscopic approach, while 690 surgeries were performed using the traditional microscopic technique. No statistically significant difference was observed in the audiological tests before (p = 0.4; Cohen's d 0.52) and after surgery (p = 0.5; Cohen's, 0.7) between patients treated with endoscopy and microscopy. Statistically significant differences were observed in post-surgical complications. Endoscopic surgery resulted in taste disorders in more patients (p = 0.03), whereas microscopic surgery led to more sensorineural hearing loss (p = 0.02) and tinnitus (p = 0.04) as post-surgical negative outcomes.ConclusionThe two techniques appear equal in terms of audiological results but differed slightly considering surgical complications. However, because the groups were highly unbalanced; therefore, our results must be considered preliminary and interpreted carefully.